The Growth of public debt in Coahuila, México - Zúñiga-Espinoza, Nicolás Guadalupe; Sainz-López, Celia Ruth; Zúñiga-Soto, Erick (Technium Social Sciences Journal, 2021)
The objective of this work is to show that the accelerated growth of Coahuila’s public debt occurred because the local legislation failed to limit the amounts borrowed, permitting the entirety of the Unconditional Transfers (UCT), specifically the General Participation Fund (GPF), to be granted as security for the loans. The results show that during the period 2000-2016, the average annual growth in the public debt was 21%. In addition, 94.3% of the GPF was pledged as security, leaving 5.7% of this income source to meet local public spending needs. Furthermore, of the seven loans obtained in 2018 and 2019, five of them were used for refinancing purposes and the other two to address liquidity shortfalls.